2015
DOI: 10.1186/s13731-015-0031-7
|View full text |Cite
|
Sign up to set email alerts
|

The impact of corporate characteristics on the financial decisions of companies: evidence on funding decisions by Italian SMEs

Abstract: Small and medium enterprises (SMEs) represent a large percentage of the corporate tissue of developed countries, but they do not have adequate attention. In fact, various researchers have focused their studies on larger and well-known companies. This paper aims to investigate the impact of corporate characteristic on the financial choices of SMEs, with a specific focus on agro-food micro companies. Access to finance is vital in business start-up, development and growth for SMEs, all with very different needs a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 28 publications
2
22
0
1
Order By: Relevance
“…For example, Gartner (2012) reveals firm characteristics, such as the potential sales revenue, the qualification and legitimacy of the business will affect the acquisition of external sources of financing. Others have done similar analysis (Rossi et al, 2015;Coleman et al, 2016). Rocca et al (2018) points out that the firm-specific and macroeconomic moderators moderate the baseline relationship between cash holdings and SME performance.…”
Section: Financing Ecology Index Systemmentioning
confidence: 96%
See 1 more Smart Citation
“…For example, Gartner (2012) reveals firm characteristics, such as the potential sales revenue, the qualification and legitimacy of the business will affect the acquisition of external sources of financing. Others have done similar analysis (Rossi et al, 2015;Coleman et al, 2016). Rocca et al (2018) points out that the firm-specific and macroeconomic moderators moderate the baseline relationship between cash holdings and SME performance.…”
Section: Financing Ecology Index Systemmentioning
confidence: 96%
“…The political and economic environment is also an important factor influencing the financing behavior of enterprises (Bushman, Piotroski, & Smith, 2004; M. L. Rocca, Staglianò, T. L. Rocca, Cariola, & Skatova, 2018). In addition to the external environment, including economic, political and financial environment mentioned above, some scholars focus on the internal characteristics of enterprises (Fernandes, 2011;Rossi, Lombardi, Siggia, & Oliva, 2015;Coleman, Cotei, & Farhat, 2016). The firm characteristics can affect the acquisition of external sources of financing (Gartner, 2012;Rocca et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Scholars have investigated the processes and approaches by which corporations organize, control, and direct resources to attain strategic goals [19]. Accordingly, governance in corporation, popularly known as corporate governance, gained an audience due antisocial behavior among corporations, collapse and bankruptcy, hostile takeovers, and the belief that corporate governance can improve firm's performance and market share [20]. In their influential work, Rossi et al [20] highlighted that corporate characteristics as a subcomponent of corporate governance can shape financial decisions and activities of firms.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…Accordingly, governance in corporation, popularly known as corporate governance, gained an audience due antisocial behavior among corporations, collapse and bankruptcy, hostile takeovers, and the belief that corporate governance can improve firm's performance and market share [20]. In their influential work, Rossi et al [20] highlighted that corporate characteristics as a subcomponent of corporate governance can shape financial decisions and activities of firms. On the other hand, corporate governance ensures that counterproductive actions and activities of individuals are detected and subsequently prevented [21].…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…Rossi, Lombardi, Siggia, and Oliva (2016) conceptualized the impact of corporate characteristics on the financial decisions of companies: evidence of funding decisions by Italian SMEs and found that there is a correlation between business size and financial decision. Moreover, it was revealed that managerial skills and experiential learning, access to, and accumulation of financial resources also increases over time with firm age.…”
Section: International Journal Of Research Studies In Management 15mentioning
confidence: 99%